Jawabanmu

2014-08-03T14:23:28+07:00
A.
(- 2/3)^4 × (1/2 - 1/6)²
= (- 16/81) × (1/3)²
= (- 16/81) × 1/9
= - 16/729

b. 
(-5)³ × (1/15)² × (10/4)^4 × (9/5)^5
= (-125) × 1/225 × 10000/81 × 6561/625
= 5/9 × 10000/81 × 6561/625
= 328050000/455625
= 720

c. 
3x² × y³ × (2y)²
   24x
= 3.2² × 3³ × (2.3)²
     24.2
= 3.4 × 27 × 6²
      48
= 12 × 27 × 36
     48
= 324 × 36
     48
= 11664
     48
= 243

d. 
(2/3x)² × (3/4) (-y)³ 
         xy²
= (2/3 . 1/2)² × (3/4) (- 1/3)³ 
        (1/2 . 1/3)²
= (2/6)² × (3/4) . (- 1/27)
         (1/6)²
= 4/36 × 3/108 
        1/36
= 12/3888
      1/36
= 1/324 × 36/1
= 36/324
= 1/9

e. 
3p²q × (-3)^4 × 4 (q/p)²
(-2p)² × (-3q)³
= 3.4².6 × (-3)^4 × 4 (6/4)²
   (-2.4)² × (-3.6)³
= 3.16.6 × 81 × 4 . 36/16
   (-8)² × (-18)³
= 288 × 81 × 9
    64 × (-5832)
= 23328 × 9
   373248
= 16 × 9
= 144

ket: (titik) itu kali (×)

maaf kalo salah :) dan lain kali coba untuk menjawab/latihan sendiri :)
2014-08-03T14:37:25+07:00
A . ( - 2/3 )⁴  x ( 1/2 - 1/6)²
= (-16/81) x (2/6)²
= (-16/81) x (4/24)
= (- 64 / 1944)

b. (-5)³ x (1/15)² x (10/3)⁴ x (9/5)²
= -125 x (1/225) x (10000/27) x (81/25)
= -101250000 / 151875

c. 3x² . y³ . ( 2y)² /24x  x= 2 , y= 3
= 3.2² . 3³ . (2.3)² / 24.2
= 3.4 . 27 . 6² / 48
= 12 x 27 x 36 / 48
= 243

d. (2/3 x)² . (3/4) . (-y)³ / xy²  x = 1/2  y = 1/3
= (2/3 x 1/2 )² x (3/4) . (-1/3)³ / 1/2 x 1/3²
= (2/6)² x 3/4 . (-1/27) / 1/2 x 1/9
= (4/36) x 3/4 . (-1/27) / 1/18
= -12 / 3888 / 1/18
= -12/3888 x 18/1
=-216/3888

e. 3p²q x (-3)⁴ x 4 (q/p)2  / (-2p)² x (-3q)³
= 3.4².6 x (-81) x 4 (6/4)² / (-2.4)² x (-3.6)³
= 288 x (-81) x 4 (36/16) / (-8)² x (-18)³
= -3359232 / 16 / 64 x 5832
= -3359232/16 / 373248
= -3359232/16 x 1/373248
= -3359232/5971968

maaf kalo salah